2019
DOI: 10.1007/978-3-030-30281-8_1
|View full text |Cite
|
Sign up to set email alerts
|

End-User Probabilistic Programming

Abstract: Probabilistic programming aims to help users make decisions under uncertainty. The user writes code representing a probabilistic model, and receives outcomes as distributions or summary statistics. We consider probabilistic programming for end-users, in particular spreadsheet users, estimated to number in tens to hundreds of millions. We examine the sources of uncertainty actually encountered by spreadsheet users, and their coping mechanisms, via an interview study. We examine spreadsheet-based interfaces and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Convertino et al [24] found that spreadsheet users did not take full advantage of the data available due to a gap in their quantitative analytical skills. Others have explored the strategies users apply to cope with uncertainty in their data [11][12][13].…”
Section: Background: the Problem Of Structure In Spreadsheets 21 Stud...mentioning
confidence: 99%
“…Convertino et al [24] found that spreadsheet users did not take full advantage of the data available due to a gap in their quantitative analytical skills. Others have explored the strategies users apply to cope with uncertainty in their data [11][12][13].…”
Section: Background: the Problem Of Structure In Spreadsheets 21 Stud...mentioning
confidence: 99%
“…Spreadsheets and databases have been an area of focus for some of this work. The most widespread end-user programming tool is the spreadsheet, where users can make use of tools such as formulas to serve their own purposes (Nardi 1993) and PPLs have been explored in this context (Geddes et al) (Borghouts et al 2019;Blackwell et al 2019). In the context of databases, BayesDB (Mansinghka et al 2015) is a general platform that uses program synthesis approaches that allow end-users to create queries for a database to build models using a SQLlike language.…”
Section: End-user Approaches To Probabilistic Programming Languagesmentioning
confidence: 99%
“…This translates to improved collaboration, scalability, and operational efficiency [1]. A significant trend in software technology is the rise of interactive applications built not by professional developers, but by domain experts leveraging computational tools to achieve their goals [2].…”
Section: Introductionmentioning
confidence: 99%
“…The global EUC market is estimated at USD 10.3 billion in 2022 and is projected for an 11% CAGR by 2032, reflecting the growing demand for EUC solutions driven by digital transformation across industries efficiency [1]. Research has shown that spreadsheets are a form of code, with spreadsheet users acting as end-user programmers [2]. Excel, specifically, remains one of the most popular end-user programming environments, with its importance in the business world continuing to rise [3].…”
Section: Introductionmentioning
confidence: 99%